Enrichment of specific microbial communities by optimum applied voltages for enhanced methane production by microbial electrosynthesis in anaerobic digestion. (March 2020) - Flores-Rodriguez, Carla; Min, Booki
Highlights: Applied voltage significantly affected the microbiome distribution in MES-AD. Hydrogenotrophic methanogens was favorably enriched on the cathode at 1.0 V. Syntrophic growths was found on the cathode for enhanced methanogenic process. The abundance of methanogen was observed on the anode with exoelectrogens. Abstract: This study investigates the distribution of microbiome in microbial electrosynthesis systems at different applied voltages (0.5, 1.0, and 1.5 V) for methane production. Results revealed that more favorable conditions for methane production were observed with 1.0 V applied voltage. In Venn plots, the bioelectrodes at 1.0 V had higher numbers of unique operational taxonomic units compared to those at 0.5 and 1.5 V. Hierarchical cluster, non-metric multidimensional scaling, and principal component ordinate analyses revealed that the biocathode at 1.0 V clustered separately from the rest of the biofilms mainly because of the quantitative differences in the microbial distribution. Taxonomically, exoelectrogens ( Geobacter spp.) dominated the bioanode at 1.0 V, while the syntrophic assemblages of hydrogen-producing bacteria (i.e., Bacteroidetes and Firmicutes ) and hydrogen-consuming methanogens (i.e., Methanobacterium sp.) existed in the biocathode. These results suggest that the optimum applied voltage enriched specific microbial communities on the anode and cathode for enhanced methane production.